Medium-term impact of the SARS-CoV-2 mRNA vaccine against disease activity in patients with systemic lupus erythematosus. Issue 1 (12th August 2022) - Yoshida, Tsuneyasu; Tsuji, Hideaki; Onishi, Akira; Takase, Yudai; Shirakashi, Mirei; Onizawa, Hideo; Hiwa, Ryosuke; Kitagori, Koji; Akizuki, Shuji; Nakashima, Ran; Tanaka, Masao; Yoshifuji, Hajime; et al.
Abstract : Objectives: Numerous case reports have referred to new onset or flare of SLE after SARS-CoV-2 messenger RNA (mRNA) vaccines. Several observational studies showed that the short-term flare rate of SLE after SARS-CoV-2 vaccination is low. However, well-controlled clinical surveys are unavailable and the medium-term impact of the SARS-CoV-2 mRNA vaccines against the flare of SLE is uncertain. Therefore, we aimed to analyse the association between vaccination and medium-term subjective and objective disease activities of SLE and flares using matched pair methods. Methods: Altogether, 150 patients with SLE from the Kyoto Lupus Cohort were included. Patients who received two doses of the SARS-CoV-2 mRNA vaccines were 1:1 matched with unvaccinated patients based on the first vaccination date. The outcome measures were the SLE Disease Activity Index-2000 (SLEDAI-2K), the Japanese version of the SLE Symptom Checklist Questionnaire (SSC-J) and the Safety of Estrogens in Lupus Erythematosus National Assessment-SLEDAI flare index at 30, 60 and 90 days after vaccination. Results: SLEDAI-2K levels were not significantly different in vaccinated and unvaccinated patients with SLE at 30, 60 and 90 days after the second vaccination (adjusted estimate (95% CI): 30 days: −0.46 (−1.48 to 0.56), p=0.39; 60 days: 0.38 (−0.64 to 1.40), p=0.47; 90 days: 0.40 (−0.54 to 1.34), p=0.41). Similar results were observed in the SSC-J score (adjusted estimate (95% CI), 30 days: 0.05 (−1.46 to 1.56), p=0.95; 60 days: −0.63 (−2.08 to 0.82), p=0.40; 90 days: 0.27 (−1.04 to 1.58), p=0.69) and flare index (adjusted OR (95% CI), 30 days: 0.81 (0.36 to 1.85), p=0.62; 60 days: 1.13 (0.50 to 2.54), p=0.77; 90 days: 0.85 (0.32 to 2.26), p=0.74). Conclusion: SARS-CoV-2 vaccination did not significantly influence the medium-term subjective and objective disease activities or flares of SLE until 90 days after the second vaccination.